(untitled) (International Journal of Nursing Education, 2020)
Nursing care is the core of any nursing education curriculum. Developing teaching and learning strategiesto enhance skills development and response to student learning need is challenging for educators. Thiswas a developmental study produced instructional teaching media. There were 95 seconds year nursingstudent participated in the study by using purposive sampling. The two focus group was conducted in orderto gather the instructional media needed. The instructional media then was develop based on the studentdemanded. The instructional media quality was assessed by three experts and comprehensively assessed bynursing students and made amendments as suggested. Data were collect by using two research instrumentsconsisted of 1) nursing practice assessment form 2) satisfaction assessment form. Data were analysis usingdescriptive statistic, and one sample t-test. The results revealed that the instructional media of fundamentalnursing practice skills according to standard criteria greater than 80/80. The students had significantly highermean score of fundamental nursing skills suctioning, dressing, and drug administrating practice than criticalstandard (t=13.63, 13.38, and 19.89 respectively, p<.001). The findings suggested that the instructionalmedia developing in conjunction with the student desired was effective in improving fundamental nursingskills and satisfaction.